Underwriting Process (Risk Selection) Marine Hull Case Study at PT. Jasa Raharja Putra Insurance - Pribadi, K H (KnE Social Sciences, 2018)
Many people realize the importance of knowing insurance products in a professional manner to minimize the risks that will occur in the business. Products from insurance companies are now growing very rapidly including products for life insurance, health insurance and loss insurance. With so many alternative choices of insurance products, we become more literate and follow the development so that we can choose the right insurance products that we need. Insurance companies must also be able to educate the communities, especially the urban and rural communities, particularly the rural areas of Kalimantan, Sulawesi, Papua, which uses water transportation. Keywords: insurance product, financial protection, investment